Improving the Ability to Read Al-Qur'an Using Flash Card Media in Early Childhood in Al-Qur'an Education Park: Peningkatan Kemampuan Membaca Al-Qur’an Menggunakan Media Flash Card Pada Anak Usia Dini Di Taman Pendidikan Al-Qur’an - Nur Kholifatul Mufridha; Istikomah Istikomah (Academia Open, 2022)
This article aims to determine the use of Flash Card Media in improving the ability to read the Qur'an in early childhood, increase the ability to read the Koran in early childhood using Flash Card Media, and analyze the factors of using Flash Media. Card in improving the ability to read the Koran in early childhood. The research approach used is non-CAR descriptive qualitative research with data obtained from interviews, observations, and documentation. The results showed that the use of Flash Card Media in improving the ability to read the Qur'an in early childhood has been maximally achieved and has a very large influence in implementing learning, as well as learning materials and the ability of educators to be professional in improving the ability to read the Qur'an. 'an in early childhood by using flash card media.